A review of leadership approaches in the industrial revolution of 4.0 era - Zulkifle, Siti Liyana Amalina; Omar, Siti Sarah; Mahadi, Normahaza; Zainal Arifin, Zailin; Yaakop, Azizul Yadi (UTHM Publisher, 2021)
This research paper was conducted to review the leadership approaches being utilized by leaders in maneuvering the digital era during Industrial Revolution 4.0. The information was retrieved by reviewing journal articles from various sources in the range of year 2015 until 2020. The study found that there are eight leadership approaches in the Industrial Revolution 4.0 and these are traditional leadership, agile leadership, diversity leadership, ethical responsibility, system leadership, technology leadership, entrepreneurial leadership and adaptive leadership. This paper also emphasized the challenges of leadership faced by the leaders in this IR 4.0 era such as innovation, talent acquisition and development and leading change that have to be encountered by leaders. Finally, the findings of the paper would provide managerial contributions to leaders in facing those challenges of Industrial Revolution 4.0 and at the same time manage to lead effectively during this new digitalization era.